A policy for the size of individual unemployment accounts - Rubén Castro; Michael Weber; Gonzalo Reyes (IZA Journal of Labor Policy, 2018)
Individual unemployment accounts (IUAs) attenuate the moral hazard attached to unemployment insurance. However, the available literature provides no policy recommendation about what percentage of the contributions should go to IUAs. We propose criteria of actuarial neutrality and use a simple job search model to argue that a sizable proportion of the contributions could go to IUAs without changing benefits and contribution rates, and therefore not negatively affecting well-being. We derive this result from a model, first, and then use simulations to show that it also holds in more realistic settings and different labor market dynamics.
Keywords: J64; J65; H21; 330; Social security; Unemployment insurance; Unemployment accounts; Moral hazard